Lingual Investigation of President Soekarno Speech: A Report - Samuel Latupeirissa, David; Darma Laksana, I Ketut; Artawa, Ketut; Sosiowati, IGAG (e-Journal of Linguistics; Vol 13 No 2 (2019): e-jl-July, 2019)
The current research aims at investigating the most important speech of Soekarno and the ideologies behind the speech. Since Soekarno was the proclaimer of Indonesian independence as well as the first president of Indonesia, we would claim that his speeches were important to be investigated. Among the speeches, we tried to reveal the most important one through a lingual investigation. This investigation was based on grounded theory and hermeneutic theory. It was focused on the text as a part of the language. The results have shown that the most important speech of Soekarno is the speech entitled, ‘ Tahun Berdikari’. It is viewed as a high novelty finding because there is no researcher who has ever claimed ‘Tahun Berdikari’ as the most important speech in the history of Indonesia. The speech contained three main ideologies, namely (1) unity as the most important thing for Indonesians, (2) revolution must be in the Indonesian soul, and (3) imperialism and capitalism as Indonesia’s main enemy.